Functional relationship between peripheral thermosensation and behavioral thermoregulation - Suito, Takuto; Tominaga, Makoto (Frontiers in Neural Circuits, 2024)
Thermoregulation is a fundamental mechanism for maintaining homeostasis in living organisms because temperature affects essentially all biochemical and physiological processes. Effector responses to internal and external temperature cues are critical for achieving effective thermoregulation by controlling heat production and dissipation. Thermoregulation can be classified as physiological, which is observed primarily in higher organisms (homeotherms), and behavioral, which manifests as crucial physiological functions that are conserved across many species. Neuronal pathways for physiological thermoregulation are well-characterized, but those associated with behavioral regulation remain unclear. Thermoreceptors, including Transient Receptor Potential (TRP) channels, play pivotal roles in thermoregulation. Mammals have 11 thermosensitive TRP channels, the functions for which have been elucidated through behavioral studies using knockout mice. Behavioral thermoregulation is also observed in ectotherms such as the fruit fly, Drosophila melanogaster. Studies of Drosophila thermoregulation helped elucidate significant roles for thermoreceptors as well as regulatory actions of membrane lipids in modulating the activity of both thermosensitive TRP channels and thermoregulation. This review provides an overview of thermosensitive TRP channel functions in behavioral thermoregulation based on results of studies involving mice or Drosophila melanogaster.